Rank of India in Ease of Doing Business During Period of 2014 to 2018 - Gajjar, Kiran (SFIMAR Research Review, 2018)
Today, India is the one of the fastest growing economies in the world. The Government of India has under taken various measures to improve position of India in Ease of Doing Business. The emphasis has been on rationalization and simplification of the existing laws and utilization of ICT (Information and Communication Technology) to make governance more efficient and effective. Initiative of Indian Government improved rank of India in the Ease of doing Business Index from 142 in 2014 to 100 in 2017 and 77t in 2018. The World Bank released its latest Doing Business Report (DBR, 2019) on 31-10-2018. India has recorded a jump of 23 positions against its rank of 100 in 2017 to be placed now at 77th rank among 190 countries assessed by the World Bank. India's leap of 23 ranks in the Ease of Doing Business ranking is significant considering that last year India had improved its rank by 30 places, a rare feat for any large and diverse country of the size of India. As a result of continued efforts by the Government, India has improved its rank by 53 positions in last two years and 65 positions in last four years. This research has been conducted to assess the improvement in the ease of doing business in the country. The scope and relevance of the research pertains to know the co-efficient of success in ease of doing business. The survey pertains to analyse the impact of dynamic policy reforms undertaken by the government at the ground level.